Cultivation of Chlorella on brewery wastewater and nano-particle biosynthesis by its biomass. (July 2016) - Subramaniyam, Vidhyasri; Subashchandrabose, Suresh Ramraj; Ganeshkumar, Vimalkumar; Thavamani, Palanisami; Chen, Zuliang; Naidu, Ravi; Megharaj, Mallavarapu
Highlights: Nutrients in brewery wastewater were efficiently utilised by Chlorella sp. MM3. Substantial microalgal biomass obtained from brewery wastewater was used for iron nanoparticle synthesis. Algal biomolecules act as reducing and capping agents in iron nanoparticle synthesis. First report of nanoparticle synthesis using microalgae coupled with brewery wastewater remediation. Abstract: This study investigated an integrated and sustainable approach for iron nanoparticles synthesis using Chlorella sp. MM3 biomass produced from the remediation of brewery wastewater. The algal growth characteristics, biomass production, nutrient removal, and nanoparticle synthesis including its characterisation were studied to prove the above approach. The growth curve of Chlorella depicted lag and exponential phase characteristics during the first 4 days in a brewery wastewater collected from a single batch of brewing process (single water sample) indicating the growth of algae in brewery wastewater. The pollutants such as total nitrogen, total phosphorus and total organic carbon in single water sample were completely utilised by Chlorella for its growth. The X-ray photoelectron spectroscopy spectra showed peaks at 706.56 eV, 727.02 eV, 289.84 eV and 535.73 eV which corresponded to the zero-valent iron, iron oxides, carbon and oxygen respectively, confirming the formation of iron nanoparticle capped with algal biomolecules. Scanning electron microscopy and particle size analysis confirmed the presence of spherical shaped iron nanoparticles of size ranging from 5 to 50 nm. To our knowledge, this is the first report on nanoparticle synthesis using the biomass generated from phycoremediation of brewery wastewater.